Trail following by gliding bacteria. - Burchard, R P (1982)
Slime trails, which are deposited on surfaces by gliding bacteria and which serve as preferential pathways for gliding motility, were tested for the species specificity of their support of movement. Among the pairs of bacteria tested, a variety of gliding bacteria and a flagellated bacterium moved along trails of unrelated species. Thus, the trails did not serve as pheromones. Rather, they may have guided gliding elasticotactically. Some biological implications of this finding are considered.